GOTOWOŚĆ KOMUNIKACYJNA W PRZEBIEGU ZAJĘĆ Z MÓWIENIA W JĘZYKU OBCYM: WYNIKI BADAŃ - Pawlak, Mirosław; Mystkowska-Wiertelak, Anna (Neofilolog, 2019)
Willingness to communicate (WTC) in a second language is the outcome of mutual influences of a wide array of psychological, linguistic, educational and communicative factors, including those that are dependent on a specific situation, such as the character of a particular class or the task being performed. All of them can increase or decrease the level of WTC on a minute-by-minute basis (MacIntyre and Legatto, 2011). The aim of the study presented in this paper was to obtain greater insights into the motives underlying willingness and unwillingness to take part in a conversation in a foreign language with a view to creating in the language classroom conditions that would stimulate communication and thus contribute to the attainment of greater proficiency. More specifically, an attempt was made to determine and measure factors affecting WTC in one group of English majors, as they were engaged in a conversation class. The data were collected by means of self-reports, completed during the class, in which the levels of WTC were indicated on a scale of -10 to +10, as well as short questionnaires filled in right afterwards. A combination of quantitative and qualitative analysis showed that WTC in a conversation class is subject to constant fluctuations and made it possible to identify factors responsible for such changes.